Effect Of Omega-3 Fatty Acids On Cardiovascular Protection- A Randomised Controlled Clinical Interventional Study (Journal of Pharmaceutical Negative Results, 2023)
There is a great deal of public belief in the cardiovascular benefits of omega-3 fats. Recent trials of omega-3 fatty acids in cardiovascular issues are unclear or failed to show the significant benefit for reducing cardiovascular events. To perform a human trial of omega 3 fatty acids supplementation to test its effectiveness on cardiovascular diseases. A randomized interventional study was carried out in 145 patients in the age group of 18 or older at any risk of cardiovascular disease. Treatment period of 6 months with supplementation of daily dose of 360 mg of EPA and 480 mg of DHA for one group and to the other group, atorvastatin 10 mg was given. Biochemical and clinical evaluation was performed for the baseline, 3rd and the 6th months to assess the effectiveness of omega 3 fatty acids on cardiovascular diseases. The changes in the biochemical parameters total cholesterol, HDL, LDL and triglycerides among the omega 3 fatty acid group and statin group were as 218.17 vs 204.45, 55.24 vs 60.3, 142.9 vs 132.41and 168.95 vs 152.5 respectively with a p value of 0.0001. Omega 3 supplements have little or no effect on the risk of cardiovascular diseases according to the research. The better evidence identified in this research does not demonstrate any cardiovascular protection with the supplementation of omega 3 fats.